THE ASSEMBLING OF CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL ASSISTED BY ORIGAMI PAPER MEDIA FOR INCREASING PLANE LEARNING RESULT IN THE FIFTH GRADE OF PRIMARY SCHOOL - Wahyuningtyas, Dyah Tri (International Journal of Elementary Education, 2017)
Abstract: The objective of this study was describing the application of CTL model assisted by origami media for increasing learning result of plane circumference in the fifth grade of primary school. It was a qualitative research by using Classroom Action Research (CAR) methodology. The subject research was 43 students in the fifth grade in Bunuwetan Pakis primary school. The steps are: (1) Introduction, (2) Material presentment step (constructivism, inquiry, questioning, learning community, modelling, reflecting, and authentic assessment), conclusion and (3) Closing. The scoring result of this study was 80% in the activity of the teacher in cycle I, it included good category. In cycle II was getting 96% and including excellent category. The activity of the students was getting 67,14% and including quite active category. Besides, in cycle II it got 92,86%, involved very active category. The result study in cycle I was gotten from classical mastery 69,77% and the average score was 63,83. The cycle II was 81,39% and the average score was 80,93. Therefore, can be concluded that the assembling of CTL model assisted by origami could increase the learning result of the fifth grade in Bunuwetan Pakis Primary school.      Key words: CTL, origami, plane